Evaluation of the AHRQ Patient Safety Initiative: Synthesis of Findings - Farley, Donna O (Blackwell Science Inc, 2009)
OBJECTIVE: To present overall findings from the 4-year evaluation of the national patient safety initiative operated by the Agency for Healthcare Research and Quality (AHRQ). DATA SOURCES: Interviews with AHRQ staff, grantees, and other patient safety stakeholders; published materials; and internal AHRQ documents. STUDY DESIGN: The evaluation was structured to address a system framework of five components involved in improving safety. The initiative's contributions to improving each system component were assessed qualitatively, comparing results from three separate analyses—AHRQ's achievement of its patient safety goals, our own assessment of the initiative's activities, and independent stakeholder ratings of AHRQ's contributions. FINDINGS AND CONCLUSIONS: AHRQ has faced a daunting challenge for improving patient safety, given the complex problems of the U.S. health care system and the limited resources AHRQ has had to address them. The patient safety initiative achieved strongest progress for its contributions to knowledge of patient safety epidemiology and effective practices, where AHRQ has considerable experience, and to strengthening infrastructure to support adoption of safe practices. Progress was slower in establishing a national monitoring capability and dissemination of safe practices for adoption. AHRQ needs to expand efforts to apply new knowledge for stimulating use of safe practices in the field.